Food deprivation and impacts on psychic constitution: a study about the establishment of the demand in children diagnosed with malnutrition through the application of psychoanalytical evaluation at the age of three - Martins, Karla Patrícia Holanda; Lima, Maria Celina Peixoto; Simão, Gabriela Monteiro; Sousa, Allan Ratts de (Clinical Styles. The Journal on the vicissitudes of childhood, 2016)
This article is part of a line of studies whose purpose is to ponder the experience of hunger in childhood and its possible connections with the psychic constitution process. Some results of the application of the Avaliação Psicanalítica aos 3 anos (AP3) instrument, applied in a third sector institution which is reference in the treatment of infant malnutrition in the city of Fortaleza, Ceará state, Brazil, will be presented. With the analysis, it was possible to relate the prevalence of malnutrition with the processes of establishment of demand, taking into account that the privation of food may be paradoxically correlated to its refusal.